Delineating Conservation Areas for Cohabiting Species: An Example of Vernal Pond Conservation From Fort Stewart in Georgia, United States - Wang, Yicheng; Önal, Hayri; Dissanayake, Sahan T. M. (Frontiers in Ecology and Evolution, 2021)
Military installations are valuable in global biodiversity conservation as they secure representative ecosystems from land conversion and protect many threatened or endangered species. Selecting suitable areas for biodiversity conservation within military installations is a challenging problem as this must not impede military training activities. The issue gets more complicated when considering multiple cohabiting species in a metacommunity with interdependency between targeted species. In this paper, we present an example for the conservation of two cohabiting species, Gopher Tortoise (GT) and Gopher Frog (GF), located within the boundaries of a military installation, Fort Stewart, Georgia, USA. The GF depends on both locations of GT habitat (burrows) and ephemeral vernal ponds (for breeding). By extending our previous work, we developed a model that identifies the cost-efficient areas for the conservation of these two species while taking into account the dependency of GF on GT burrows. The model designs a specified number of conservation areas for the two species, where each GF conservation area covers an adequate number of vernal ponds for the GFs to accommodate their reproduction, and each GT conservation area provides adequate habitat quality to sustain a viable GT population. The model also requires each GF site to be located close to GT sites so that the GFs could find refuge after they leave the water. We measure the conservation cost as the total distance of selected sites to the main roads in the military installation. We achieve contiguity of each conservation area by selecting sites that are adjacent to a central site of the conservation area to ensure undisrupted travel for both the GFs and the GTs. Using the model, we generated alternative configurations of conservation areas that could be considered by the land managers of Fort Stewart. Our methods are general and can be applied to other reserve site selection and land management problems with cohabiting interrelated species.